The Geography of Networks and R&D Collaborations - Scherngell, Thomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
The geography of networks and R&D collaborations, in particular the spatial dimension of interactions between organisations performing joint R&D, have attracted a burst of attention in the last decade, both in the scientific study of the networks and in the policy sector. The volume is intended to bring together a selection of articles providing novel theoretical and empirical insights into the geographical dynamics of such networks and R&D collaborations, using new, systematic data sources, and employing cutting-edge spatial analysis and spatial econometric techniques. It comprises a section on analytic advances and methodology, and two thematic sections on structure and spatial characteristics of R&D networks, and the impact of R&D networks and policy implications. The edited volume provides a collection of high-level research contributions with an aim to contribute to the recent debate in economic geography and regional science on how the structure of formal and informal networks modifies and influences the spatial and temporal diffusion of knowledge.
Editorial Introduction -- Part A: Analytic Advances and Methodology -- Part B: Structure and Spatial Characteristics of R&D Networks -- Part C: Impact of R& D Networks and Policy Implications -- Epilogue.
Keywords: Economics; Geography; Industrial organization (Economic theory).; Regional economics; Economics/Management Science; Regional/Spatial Science; Economic Geography; R & D/Technology Policy; Industrial Organization